2012
DOI: 10.1177/1533317512450066
|View full text |Cite
|
Sign up to set email alerts
|

Medication Reminder Device for the Elderly Patients With Mild Cognitive Impairment

Abstract: Reminder devices reportedly improve medication adherence in the elderly patients with mild dementia; however, the efficacy of such devices remains unexplored. Therefore, a 3-month before and after study with convenience sampling was conducted to determine the efficacy of a medication reminder device used by 18 participants (aged 81.2 ± 6.2 years) with Clinical Dementia Rating scores of 0.5 or 1. At the onset of device use, examiners visited the users’ homes to ensure that they and their caregivers understood h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 11 publications
2
36
0
2
Order By: Relevance
“…The MMSE alone may not be effective in diagnosing mild cognitive impairment . Nevertheless, a small pre–post intervention study found that reminder devices improved medication adherence in older adults with mild cognitive impairment . Thus, additional well‐designed studies with larger sample sizes are needed to identify the role of cognitive decline in medication adherence, as well as the relationship between reduction of these factors and control of chronic diseases in the elderly population …”
Section: Discussionmentioning
confidence: 99%
“…The MMSE alone may not be effective in diagnosing mild cognitive impairment . Nevertheless, a small pre–post intervention study found that reminder devices improved medication adherence in older adults with mild cognitive impairment . Thus, additional well‐designed studies with larger sample sizes are needed to identify the role of cognitive decline in medication adherence, as well as the relationship between reduction of these factors and control of chronic diseases in the elderly population …”
Section: Discussionmentioning
confidence: 99%
“…However, these systems can be expensive and impractical to install and manage. Automated reminder devices may be easier to apply to the growing population of patients with AD, but do not have the benefit of increasing human contact with the patient [59]. …”
Section: Interventions To Improve Adherence In Admentioning
confidence: 99%
“…Specifically, the authors reported the necessity for coordinated, tailored and flexible care processes [64]. While acknowledging that in the Australian setting a range of services and programs aim to support people living in the community (e.g.…”
Section: Health Service Provision For Older People With Cognitive Impmentioning
confidence: 99%